La rencontre du paysage - Joël Bouderlique (Projets de Paysage)
What we call ‘landscape’ is the instant when a milieu appears to an individual. It assumes their meeting. This one rests on a capacity of astonishment which opens to a rhythm common to both, that of the original uniqueness from where they exist their own being. This process is possible only in break with the presentation of the habitual environment which constitutes in separated ob-jects the world and subject. It is in the transition from sensation to feeling that the subject and the world find their primordial constituting union which appears there as landscape. This text tries to engage with this primeval situation of every moment by clarifying examples of natural and artificial landscapes. It is aimed at contributing to the creation of such instants by the landscapists.